1994
DOI: 10.1016/0020-7292(94)90568-1
|View full text |Cite
|
Sign up to set email alerts
|

Maternal genitalChlamydia trachomatisinfection and the risk of preterm labor

Abstract: Routine screening and treatment of pregnant women with Chlamydia trachomatis (along with their partners) may be beneficial in reducing the incidence of preterm labor and delivery and hence the perinatal mortality rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 8 publications
2
8
0
1
Order By: Relevance
“…The perinatal mortality rate is one of the most important indicators of the quality of perinatal care. As with [7] Ngassa and [9] Orfila et al, our results suggest that C. trachomatis infection is of great importance in perinatal pathologies. The perinatal mortality rate was significantly higher in the C. trachomatis positive patients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The perinatal mortality rate is one of the most important indicators of the quality of perinatal care. As with [7] Ngassa and [9] Orfila et al, our results suggest that C. trachomatis infection is of great importance in perinatal pathologies. The perinatal mortality rate was significantly higher in the C. trachomatis positive patients.…”
Section: Discussionsupporting
confidence: 89%
“…A breakthrough in the prevention of this problem requires more data about the causes leading to premature uterine contractions. A large number of anecdotal observations suggest that C. trachomatis infections may have a causative role in the origin of premature delivery [5,7,14]. Consequently, a multicenter survey was carried out in order to determine the prevalence and risk factors for C. trachomatis infection in the pregnant population in Hungary [8] as Nyári has reported.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies were small compared to our study (less than 1,000 women included) and were published 10 to over 20 years ago. Early studies were often based on serology, which does not reliably distinguish current from past infection [9, 11, 14, 15]. One case–control study found an association between the presence of IgM anti-chlamydial antibody and preterm delivery [11].…”
Section: Discussionmentioning
confidence: 99%
“…In women, Chlamydia causes cervicitis, urethritis, endometritis and scarring of fallopian tubes, with consequent infertility, inflammatory pelvic disease, ectopic pregnancy and adverse pregnancy outcome. 5,6,13,16,17,21 Screening of women for chlamydial infection has been recommended by different organizations, including the U.S. Centers for Disease Control and Prevention, 20 as various screening programs have been shown to significantly decrease C trachomatis prevalence in some regions. A reliable estimate of the prevalence of genital chlamydial infection in India is not available.…”
Section: Cytologymentioning
confidence: 99%